The Role of KM on the Relationship Between ERM and CA - Yuwono, Matias Andika; Ellitan, Lena (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study explores the critical role of Knowledge Management (KM) in mediating and moderating the relationship between Enterprise Risk Management (ERM) and Competitive Advantage (CA). Methodology: This paper synthesizes existing research through a literature review of studies focusing on KM, ERM, and CA. Result: The research reveals that KM strengthens ERM's ability to manage risk by improving decision-making processes and enhancing organizational responsiveness to risks. Conclusions: Knowledge Management (KM) strengthens Enterprise Risk Management (ERM) and supports Corporate Advantage (CA) by improving decision-making, fostering innovation, and enhancing adaptability. KM acts as both a moderator and mediator, aligning risk strategies with business goals. As key intangible assets, KM and ERM help firms stay competitive. In high-risk sectors, integrated KM-ERM boosts responsiveness and performance, though challenges like silos and staff gaps require better communication and systems. Limitations: The study's limitation lies in its review nature, relying on secondary data from existing literature. Contribution: This study contributes to knowledge management, risk management, and strategic management by providing insights into how organizations can leverage KM to enhance risk management practices and gain a competitive edge. It provides practical recommendations for organizations aiming to integrate KM within their ERM strategies for better decision making and risk handling.